Multipoint temperature measurements in gas flows using 1-D laser-induced grating scattering - Willman, C; Ewart, P (Springer Berlin Heidelberg, 2016)
A technique is reported for simultaneous, time- and space-resolved measurements of temperature using laser-induced thermal grating scattering, LITGS, from four points on a 1-D line. Signals from four separate points on the line, separated by 1 mm, in toluene-seeded nitrogen flows, were imaged onto a fibre-optic array and delivered to separate photo-diode detectors to record their temporal evolution from which the temperatures at each point were derived with a spatial resolution of 1 mm and a precision of 0.7% at atmospheric pressure. Effects of variation of composition on the accuracy of the measurements were compensated by a calibration method providing good agreement with values inferred from thermocouple measurements. Temperature gradients at the boundary between parallel gas flows and at the surface of hot and cold surfaces were measured with a resolution of 5 Kmm-1 . Extension of the technique to more measurement points and improvements in spatial resolution are briefly discussed.